TINJAUAN HUKUM ISLAM TERHADAP PERBEDAAN PEMBAYARAN UPAH JASA GRABBIKE SECARA TUNAI DAN NON TUNAI - Waluyo Sudarmaji (JURNAL HAKAM, 2020)
The problem in this research is whether the difference between cash and non-cash payment of GrabBike wages accompanied by additional costs unilaterally by the GrabBike driver is in accordance with Islamic law. Data analysis using descriptive qualitative analysis method. The results of this study are that according to Islamic law there is a difference between cash and non-cash payment of GrabBike service wages because in accordance with ijarah dzimmah, namely rental benefits for buying and selling services, Grab and Ovo have the right to provide promo rates or discounts as a form. Prizes and the giving of legal prizes are permitted by the syara 'because in this case the passenger and driver are not disadvantaged but instead benefited, but in connection with the additional wages that the GrabBike driver unilaterally demands for various reasons, Grab does not justify Islamic law is not in accordance with the pillars of the ijarah contract because one party feels forced.